URGENSI PENGUATAN IDENTITAS KEWARGANEGARAAN SUBNASIONAL DI KOTA PADANG PASCA GEMPA 2009 STUDI TENTANG REPOSISI ETNIS CINA TERHADAP KEBIJAKAN PUBLIK DAN POLITIK LOKAL - Jumhari Jumhari (Jurnal Elektronik WACANA ETNIK, 2013)
After earthquake disaster occurred on 30 September 2009, the government of Padang city and its people is not only faced with the question on Padang economic recovery and rebuilding efforts on city infrastructure but also on isssue on how to reconstruct the social structure of local population which was torn due to the handling and management of victims of post days of earthquake. One main issue is the emergence of apriori attitude felt by Chinese residents toward the neglected and discriminative attitude of government. However, it raises social solidarity amongst them post earthquake. As a minority group, Chinese is not only susceptible to economic issues, they are also vulnerable to social and cultural issues, including in the case of post-earthquake in Padang. Strengthening on subnational awareness within Chinese society reemerges when Padang municipal government in the early 2012 is about to demolish unload Gate of Friends Amical Association (Gapura Himpunan Tjinta Teman), one of Chinese cultural symbols built by Chinese ethnic in Padang as a form of solidarity. Thus, the campaigns and slogans glorifying the recognition of the diversity of life constantly voiced by Padang goverment becoming counterproductive and paradox in viewing social phenomena and empirical facts concerning government relations and their minority citizens. It is because the efforts to rebuild the pieces of social solidarity that has been torn, is in fact, it is not a simple task. To establishing uniformity in diversity takes commitment and consistent recognition as to create city residents that is more cultured and dignified in the future. This paper sees the struggle of Chinese people in Padang in their effort to reclaim the cultural symbols in public spaces after the earthquake occurred in 2009 and the emergence of dispute regarding the existence of Gate of Friends Amical Association (Gapura Himpunan Tjinta Teman) in Pecinan Padang area in early 2012 through field research and theoretical studies in analyzing the relationship between public policy and minority groups.